Cadmium content in aquatic organisms of the Caspian Sea - T. S. Ershova; V. F. Zaitsev; V. A. Chaplygin; A. S. Khursanov (Юг России: экология, развитие)
Aim. Reveal the distribution of cadmium in the components of the ecosystem of the Caspian Sea.Materials and Methods. The sampling was carried out according to generally accepted methods, the determination of heavy metals was carried out by the method of atomic absorption spectroscopy using an atomic absorption spectrometer with electrothermal atomization MGA‐915 MD.Results. As a result of the studies carried out, it was found that the bottom sediments of the Middle Caspian were distinguished by a greater accumulation of cadmium than the North Caspian. Invertebrates of the Caspian Sea accumulate cadmium from water and soil, with the exception of shrimp, for which water is the only source of metal. Among the taxonomic groups of organisms studied, molluscs of the genus Didacna are cadmium accumulators. In the body of the Russian and Persian sturgeons, cadmium is mainly accumulated in the kidneys.Conclusion. Coefficients of cadmium accumulation in the organs and tissues of Russian and Persian sturgeons, black‐backed herring and Dolginsky herring relative to their food objects indicate that cadmium is able to accumulate in food chains.